Genetic evaluation of lifetime performance of Phule Triveni cows by univariate and multivariate methods - AMBHORE, G S; SINGH, AVTAR; DEOKAR, D K; SINGH, MANVENDRA; SAHOO, S K; DIVYA, P (The Indian Journal of Animal Sciences, 2017)
Data pertaining to 509 Phule Triveni cows sired by 102 bulls maintained at Research-Cum Development Projecton Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri District Ahmadnagar (Maharashtra) were analysed to studythe performance of Phule Triveni cows for lifetime traits. Least-squares means and genetic parameters were estimated for different lifetime traits. The observed least squares means for actual life time milk yield (ALTMY), herd life (HL), productive life (PL) and breeding efficiency (BE) were 12767 ± 207 kg, 2863 ± 29 days, 1875 ± 28 days and77.00 ± 0.71%, respectively. The estimates of heritability (h2) for all these lifetime traits under univariate methods(LSML and REML) were 0.15 ± 0.11 and 0.22 ± 0.08 for ALTMY, 0.10 ± 0.12 and 0.19 ± 0.06 for HL, 0.10 ± 0.11 and 0.16 ± 0.05 for PL and 0.01 ± 0.11 and 0.10 ± 0.07 for BE, respectively. The h2 estimates obtained by REML method were higher as compared to LSML. The h2 estimates for ALTMY under two traits models were 0.27 ± 0.08, 0.20 ± 0.08 and 0.20 ± 0.06 for ALTMY + PL, ALTMY + HL and ALTMY + BE traits combinations, respectively. The observed estimates of h2 for ALTMY in combination with PL were higher than the estimates obtained under univariate model by REML method. The estimates of h2 for ALTMY were 0.54 ± 0.03, 0.54 ± 0.06 and 0.49 ± 0.02 for ALTMY + PL + HL, ALTMY + PL + BE and ALTMY + HL + BE traits combinations, respectively. The h2 estimates of ALTMY under three trait models were quite high, positive and significant compared to two trait and unitrait models by REML method. The lifetime trait combinations of ALTMY, HL, PL and BE could be used for genetic evaluation and selection of cows in the herd at any point of time. The genetic and phenotypic correlations among the lifetime traits in the present study were 0.90 ± 0.10 and 0.92 ± 0.11, 0.88 ± 0.17 and 0.98 ± 0.11 and 0.17 ± 0.08 and 0.06 ± 0.26 within ALTMY and PL, ALTMY and HL and ALTMY and BE, respectively. The high genetic and phenotypic correlations between ALTMY, HL and PL revealed that selection can be based on any one of these lifetime traits to bring improvement in other lifetime traits.